2011
DOI: 10.1158/1078-0432.ccr-10-2315
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Cancer Germline Antigen Promoter and Global DNA Hypomethylation in Ovarian Cancer: Association with the BORIS/CTCF Expression Ratio and Advanced Stage

Abstract: Purpose: Cancer germline (CG) antigens are frequently expressed and hypomethylated in epithelial ovarian cancer (EOC), but the relationship of this phenomenon to global DNA hypomethylation is unknown. In addition, the potential mechanisms leading to DNA hypomethylation, and its clinicopathologic significance in EOC, have not been determined.Experimental Design: We used quantitative mRNA expression and DNA methylation analyses to determine the relationship between expression and methylation of X-linked (MAGE-A1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 48 publications
7
96
0
Order By: Relevance
“…In epithelial ovarian cancer, the BORIS/CTCF expression ratio is also associated with a higher stage of tumor and decreased rate of survival (Woloszynska-Read et al, 2011). It has been suggested that the expression of BORIS displaces CTCF in the genome and leads to proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial ovarian cancer, the BORIS/CTCF expression ratio is also associated with a higher stage of tumor and decreased rate of survival (Woloszynska-Read et al, 2011). It has been suggested that the expression of BORIS displaces CTCF in the genome and leads to proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that BORIS regulates expression of genes encoding other CTAs including MAGE-A1, SPANX, and NY-ESO-1 (30,31). Recent publications suggested BORIS was involved in DNA hypomethylation in cancers that is important for derepression of CTAs expression (32,33). These studies suggest that BORIS is an important regulator of CTA expression in cancer cells.…”
Section: Ctcfmentioning
confidence: 93%
“…We also analyzed MAGEA11 expression in human EOC, which has proven a useful disease model to study CG antigen gene regulation. [18][19][20] Oncomine analysis of the Cancer Genome Atlas (TCGA) high-grade serous ovarian cancer data revealed significant elevation of MAGEA11 expression in EOC as compared with normal ovary (Fig. 2A).…”
Section: Dna Methylationmentioning
confidence: 99%